Measuring Organizational Capital - CAI, WEI; PRAT, ANDREA; YU, JIEHANG (Journal of Accounting Research, 2026)
ABSTRACT Prior research has pointed to differences in organizational capital as a reason for the persistent performance discrepancies among otherwise similar firms. In this paper, we develop and validate a new measure of organizational capital. Based on over a million crowd‐sourced employee reviews scraped from Glassdoor, we construct the measure of organizational capital at the firm‐year level using the word embedding model and ChatGPT‐generated synthetic reviews. Our measure varies over time in accordance with macro trends, and differs both across and within firms, reflecting firm heterogeneity and major internal changes. We validate our measure by testing empirical predictions of the properties of organizational capital discussed in prior literature. Our findings suggest that this measure captures a slowly evolving intangible asset that is significantly associated with firm performance and top management's influence, aligning with the conceptualization of organizational capital by Dessein and Prat. We further showcase applications of our measure in accounting, economics, finance, and management literature. Taken together, the paper provides implications for various stakeholders who are interested in assessing and managing firms' organizational capital.